An ex-post impact assessment of IFPRI's GRP22 program, water resource allocation: Productivity and environmental impacts - Bennet, Jeffrey W. (International Food Policy Research Institute, 2013)
The performance of the International Food Policy Research Institute’s (IFPRI’s) research program that focuses on water resource issues is reviewed for the period 1994–2010 around the three themes that constitute the program: global modeling, river basin modeling, and institutions.